FACTORS ASSOCIATED WITH INCOMPLETION OF IMMUNIZATION AS SCHEDULED AMONG CHILDREN GOING FOR IMMUNIZATION AT NABWERU HEALTH CENTRE III, NANSANA MUNICIPALITY. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Akongo , Irene Georgina (Student's Journal of Health Research Africa, 2023)
Introduction Immunization is a proven tool for controlling and eliminating life-threatening infectious diseases and it is estimated to avert 2 to 3 million deaths each year. The agent in a vaccine stimulates the body's immune system to recognize the agent as foreign, destroy it, and "remember" it. In this way, the immune system can more easily recognize and destroy any of these microorganisms in future encounters. Objective of the study. The study was intended to determine factors associated with the incompletion of immunization as scheduled among children going for immunization at Nabweru Health Centre iii, Nansana Municipality. Methodology: The study was a descriptive cross-sectional study that involved collecting data from 100 respondents and the study employed structured questionnaires administered by the researcher and the research assistants to gather relevant data about factors associated with incompletion of immunization as scheduled among children going for immunization at Nabweru Health Centre iii, Nansana Municipality. Children were got using a systemic sampling technique. Results: Out of the 100 respondents, the Majority, 58(58%) of the children were males. The majority, 51(51%) of the respondents were of rural residence. The majority, 61(61%) gave birth at home. The majority, 64(64%) of the respondents were aware of the threat of vaccine-preventable illnesses. The majority, 56(56%) of the respondents noted that the process was a waste of time. Conclusion: The study specifically sought to find out the factors associated with incompletion of immunization among children going for immunization at Nabweru Health Centre iii, Nansana Municipality and found out that there is still a big number of children defaulting immunization as per the immunization schedule. Recommendation: The government through the M.H.O of Nansana should emphasize immunization of all children under 5 by providing all necessary resources as well as educating and encouraging caretakers to take their children for immunization.